SOLVING EXERCISES WITH PHYSICAL CONTENT IN THE MATHEMATICS LESSONS AS A PART OF FORMATION OF PUPILS’ UNIVERSAL LEARNING ACTIVITIES - Shvai, O. (Physical and Mathematical Education, 2021)
Formulation of the problem. An important task of the modern school education is the training of a creative person who can independently acquire knowledge and then use them in practice. In this regard, a problem of formation of universal learning activities of pupils becomes high relevant, mastering of which provides conditions for the self-development and self-improvement. Materials and methods. We analyze psychological, educational and methodical literature in the context of research, study and generalize the advanced pedagogical and own experience during working in educational institutions. Results. The article analyzes scientific literature on the problem of formation of pupils’ universal learning activities. The concept of "universal learning activities" is explained, the characteristic features of universal learning activities and their types are described. Emphasis is placed on the fact, that in a process of formation of universal learning activities of pupils one should take into account the specifics of the methodology of world cognition in different subjects. We justify, that solving problems with physical content in the mathematics lessons is an effective mean of forming universal learning activities. When solving such problems, pupils improve their ability to compare, analyze, summarize, translate a text into the language of mathematics, etc. Thus, all conditions are created for acquainting pupils within the school curriculum with mathematical modeling, enhancing their understanding the mathematical modelling, its types and stages, and developing the ability to build appropriate mathematical models. Conclusions. The development of pupils’ understanding of the nature of reflection of mathematical phenomena and processes of the real world, the role of mathematical modeling in scientific knowledge, plays an important role in the formation of pupils’ universal learning activities. Some methodical tips are proposed, which can help to purposefully develop the ability of pupils to build mathematical models in solving problems with physical content.